If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -1 = -2y + 2 Reorder the terms: -1 + -3y = -2y + 2 Reorder the terms: -1 + -3y = 2 + -2y Solving -1 + -3y = 2 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -1 + -3y + 2y = 2 + -2y + 2y Combine like terms: -3y + 2y = -1y -1 + -1y = 2 + -2y + 2y Combine like terms: -2y + 2y = 0 -1 + -1y = 2 + 0 -1 + -1y = 2 Add '1' to each side of the equation. -1 + 1 + -1y = 2 + 1 Combine like terms: -1 + 1 = 0 0 + -1y = 2 + 1 -1y = 2 + 1 Combine like terms: 2 + 1 = 3 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3
| 21a=56+7a | | -2q=-4q-10 | | 23+3(4x-5)=-4-6x | | 17=10h-3h+3 | | x^2-3x-3=0 | | 41+(3x+4)=0 | | 18-5(2x+3)=9-15x | | 10n=36-2n | | -11x+2y=4 | | 4x+8=10x-2(3x-4) | | 17=10h-3+3 | | 17=10-3+3 | | 16h+25h+3h-4=84 | | y=20-3y | | 7=10-3+3 | | 9c^2+6c+1=0 | | 5x+2x-3=18 | | 3x-7=11x-(8x-2) | | 20-w=6w | | 2x-3(4-x)=8+4(x-1) | | 96n+-78n+10=100 | | 91=6x+3x+10 | | 13x=21 | | 29-7(4-3x)=4x+5(x-7) | | 67-f=47 | | 13x=26 | | 13x-5=21 | | 8n=180 | | 5n=3n+8 | | 3x+18=2x-28 | | -4d+-6d+-18d+9d=19 | | -12=7s-5 |